Analysis of the Effect Degree of Operating Leverage (DOL) and Degree of Financial Leverage (DFL) On Earning Per Share (EPS) in Pt. Agung Podomoro Land Tbk - Suseno, Giri; Murnawati, Murnawati; Lubis, Nurhayani (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2023)
The purpose of this study was to determine the effect of the variable Degree of Operating Leverage and Degree of Financial Leverage partially or simultaneously on Earning Per Share. The data used in the study are secondary data, the object used in this study is PT Agung Podomoro Land Tbk for the period (2010-2019) which is listed on the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis, partially Degree of Operating Leverage has a negative and insignificant effect on Earning Per Share, and Degree of Financial Leverage has a positive and insignificant effect on Earning Per Share. The simultaneous test results show that the regression model can be used to predict Earning Per Share as evidenced by the significant value of the F test of 0.787> 0.05. The R-Square value of 0.066 indicates that the ability of the independent variables to explain the variation in the dependent variable is 6% and the remaining 94% is explained by other variables outside the research model.